The Dangers of Separating Social Justice from Multicultural Education: Applications in Higher Education - Lawyer, Gloshanda (International Journal of Multicultural Education, 2018)
This article presents the case of the author’s experience as a student in a multicultural education course. The exploration of this case expands on Cho’s (2017) theoretical linking of social justice and multicultural education by highlighting the practical dangers of disengaging social justice from multicultural education. As an alternative to critiquing the field of multicultural education, this paper focuses on the execution of social justice in a multicultural education course. Both a social justice and a multicultural education lens are applied to analyze the author’s experience in the course. Additionally, practical considerations are provided for those teaching multicultural education courses in higher education.